Enhancing Therapeutic Drug Monitoring in Inflammatory Bowel Disease: A Comparative Analysis of Rapid Point-of-Care Infliximab, Adalimumab and Anti-Drug Antibodies' Determination against ELISA - Francisco José Toja-Camba; Laura García-Quintanilla; Lorena Rodríguez-Martinez; Julia Tomine; Francisco Cajade-Pascual; Carolina Feitosa; Irene Zarra-Ferro; Manuel Barreiro-; Jaime González-López; Cristina Mondelo-García; Anxo Fernández-Ferreiro (MDPI AG, 2023)
The introduction of point-of-care (POC) assays into clinical practice in patients with inflammatory disease enables on-demand therapeutic decision making. The aim of this study was to compare the POC test Quantum blue (Bühlmann Laboratories) for infliximab (IFX), adalimumab (ADL), and its anti-drug antibodies with the traditional ELISA assay (Promonitor). A total of 200 serum samples were analyzed. Samples were classified into the following three different groups; sub-therapeutic range (IFX < 3 μg/mL and ADL < 5 μg/mL); therapeutic range (IFX: 3-7 μg/mL and ADL: 5-12 μg/mL) and supra-therapeutic range (IFX levels > 7 μg/mL and ADL levels > 12 μg/mL). Significant higher values were measured using the POC test (p < 0.001) for IFX results but no differences in ADL trough levels were observed (p = 0.3101). Spearman's correlation indicated a good correlation between the two assays (rs = 0.88 for ADL and rs = 0.93 for IFX), and McNemar's test revealed significant differences (p = 0.016) when classifying IFX samples between therapeutic and supra-therapeutic ranges but no significant differences were found among the other ranges for either IFX or ADL. These results show that we should be cautious when using these rapid measurement methods, and new targets should probably be defined for IFX when using this new analytical method.